Intra-Articular Platelet Rich Plasma vs Corticosteroid Injections for Sacroiliac Joint Pain: A Double-Blinded, Randomized Clinical Trial. Issue 7 (24th November 2021) - Chen, Allen S; Solberg, Joseph; Smith, Clark; Chi, Michelle; Lowder, Ryan; Christolias, George; Singh, Jaspal Ricky
Abstract: Objective: Using stringent inclusion criteria, a double-blinded study protocol, and fluoroscopically guided injections, we compare intra-articular sacroiliac joint platelet-rich plasma injections with intra-articular steroids. Design: Double-blind, randomized controlled trial. Setting: Two large university-based interdisciplinary spine centers. Subjects: A total of 26 patients with a positive diagnostic block (>80% relief). Methods: Subjects who had a positive diagnostic block were randomized to undergo either a fluoroscopically guided intra-articular injection of steroid or a platelet-rich plasma injection. Follow-up was at 1 month, 3 months, and 6 months. Outcomes included level of pain, as indicated on a 0- to 100-mm numeric pain rating scale, and functional disability score, obtained via the Oswestry Disability Index (ODI). Results: At 1, 3, and 6 months, both groups improved; however, subjects who received steroid injections reported lower pain scores than did subjects who received platelet-rich plasma. Using categorical data, we observed significantly more responders (defined as pain scores that improved by 50% or more from baseline) at 1 and 3 months in the group who received steroids than in the group who received platelet-rich plasma. Conclusion: Although both groups showed improvements in pain and function, the steroid group had significantly greater response and significantly more responders than did the platelet-rich plasma group.